Peculiarities of financing the economic activity of Ukrainian enterprises in today's conditions (Economics and region, 2022)
The article highlights the types of enterprise financing and identifies positive and negative factors affecting their activity. The condition was studied and a quantitative assessment was carried out on the example of JSC "LKF "Svitoch". It was revealed that today there is uncertainty in the macroeconomic situation, which has a destructive effect on the formation of Ukraine's economic relations with the European Union. Based on the analysis of the index of business expectations, it was determined that monitoring the stability of Ukrainian business is gaining relevance. Forms of sources of financing were considered, which made it possible to assess the possibilities of attracting more investments in the development of enterprises during martial law and improving cooperation with the EU. It has been established that the economic instability of the state is observed in the conditions of war, which affects the indicators of financial assets of enterprises, their ability to self-finance and independently attract foreign capital to their own business. In today's conditions, the state plays an important role in the formation of sources of financing for enterprises, because it creates various support programs and allocates grants for the development of startups. Reconstruction of Ukrainian business and assistance by the government with the help of various methods of influence, in particular integration with the EU, conducting effective activities by enterprises is one of the most important prerequisites for further expansion and technological development of business, which will further increase the economic stability and mobility of the country's economy during crisis events.
Keywords: funding sources; enterprise sustainability; 5-7-9% program; bank loans; grants; investment climate